The Tao of open science for ecology. Issue 7 (23rd July 2015) - Hampton, Stephanie E.; Anderson, Sean S.; Bagby, Sarah C.; Gries, Corinna; Han, Xueying; Hart, Edmund M.; Jones, Matthew B.; Lenhardt, W. Christopher; MacDonald, Andrew; Michener, William K.; Mudge, Joe; Pourmokhtarian, Afshin; et al.
Abstract : The field of ecology is poised to take advantage of emerging technologies that facilitate the gathering, analyzing, and sharing of data, methods, and results. The concept of transparency at all stages of the research process, coupled with free and open access to data, code, and papers, constitutes "open science." Despite the many benefits of an open approach to science, a number of barriers to entry exist that may prevent researchers from embracing openness in their own work. Here we describe several key shifts in mindset that underpin the transition to more open science. These shifts in mindset include thinking about data stewardship rather than data ownership, embracing transparency throughout the data life‐cycle and project duration, and accepting critique in public. Though foreign and perhaps frightening at first, these changes in thinking stand to benefit the field of ecology by fostering collegiality and broadening access to data and findings. We present an overview of tools and best practices that can enable these shifts in mindset at each stage of the research process, including tools to support data management planning and reproducible analyses, strategies for soliciting constructive feedback throughout the research process, and methods of broadening access to final research products.